Von Pop zum Konzept : Kunst unserer Zeit in Belgischen Privatsammlungen. - Becker, Wolfgang; Geirlandt, Karel (Aachen : Neue Galerie - Sammlung Ludwig, 1975)
Acconci, Vito ; Bochner, Mel ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Christo ; Dibbets, Jan ; Dine, Jim ; Estes, Richard ; Fulton, Hamish ; Gilbert & George ; Graham, Dan ; Kaprow, Allan ; Keienholz, Edward ; Kosuth, Joseph ; Levine, Les ; LeWitt, Sol ; Marden, Brice ; Oldenburg, Claes ; Oppenheim, Dennis ; Ryman, Robert ; Tilson, Joe ; Twombly, Cy ; Wegman, William
Von Pop zum Konzept : Kunst unserer Zeit in Belgischen Privatsammlungen, Neue Galerie - Sammlung Ludwig, Aachen, 4.10 - 9.11.1975
Duits & Engels & Nederlands
kunstcatalogus
Keywords: België